Hubugan Resiko Jatuh Dengan Kualitas Hidup Lansia Di Kawasan Rawan Bencana Gunung Merapi Balerante Kemalang Klaten - Nurhidayati, Istianna; Muflih, Muflih; Mawardi, Mawardi; Rahmah, Qori Jabal (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The aim of this study was to identify the relationship between the risk of falling and the quality of life of the elderly in disaster-prone areas of Mount Merapi, Balerante, Kemalang, Klaten. Methods: This study used correlational quantitative research design with a cross sectional approach. Respondents in this study were as many as 84 elderly who were obtained by cluster random sampling technique and according to inclusion criteria. The data collection technique used the WHOQOL-OLD questionnaire and the TUGT observation sheet. Bivariate data analysis used the Kendalls Tau statistical test. Results: The results of this study found that 85.7% of the elderly were aged (60-74 years), 52.4% of the elderly were female, 63.1% had not experienced a fall in the last 1 year, 66.7% of the elderly had a mild fall risk, and 78.6% of the elderly have a high quality of life. The study obtained p = 0.053 and r = -0.176.Conclusion: The conclused of this study is no significant relationship between the risk of falling and the quality of life of the elderly in the disaster-prone area of Mount Merapi, Balerante, Kemalang, Klaten.